Decreased heart rate variability in survivors of sudden cardiac death not associated with coronary artery disease. Issue 1 (January 1994) - Fei, L.; Anderson, M. H.; Katritsis, D.; Sneddon, J.; Statters, D. J.; Malik, M.; Camm, A. J.
Abstract : BACKGROUND–Although heart rate variability has already been studied in survivors of sudden cardiac death secondary to coronary artery disease, an assessment of heart rate variability in survivors of sudden cardiac death not associated with coronary artery disease has not been made. METHODS–10 patients with aborted sudden cardiac death not associated with coronary artery disease (seven patients with primary ventricular fibrillation and three with unclassified mild cardiomyopathy) underwent two channel 24 hour Holter monitoring in a drug free state. All subjects were in sinus rhythm and had normal atrioventricular conduction and normal cardiac function. Spectral heart rate variability was analysed on a Holter analysis system and was expressed as total (0.01-1.00 Hz), low (0.04-0.15 Hz) and high (0.15-0.40 Hz) frequency components for each hour. Heart rate variability index was calculated for the 24 hour periods. 10 age and sex matched healthy subjects were taken as a control group. RESULTS–The spectral heart rate variability over 24 hours was significantly lower in survivors of sudden cardiac death than in controls (total 38(15) v 48(14) ms; low, 25(11) v 32(13) ms; and high, 13(8) v 18(8) ms; p < 0.05 for all comparisons). The differences in the ratio of low/high (2.19(0.76) v 1.98(0.50), p = 0.132), mean heart rate (77(12) v 69(12) beats/min, p = 0.070), and heart rate variability index (38(12) v 44(16), p = 0.287) over 24 hours between survivors of sudden cardiac death and controls did not reach significance. Comparisons of the hourly heart rate variability over the 24 hour period between the two groups showed that the differences in all components of heart rate variability, low/high ratio and mean heart rate were highly significant. Furthermore, there was no significant difference in the maximum hourly heart rate variability over the 24 hour period. The minimum hourly heart rate variability was, however, significantly lower in survivors of sudden cardiac death than in controls (total, 20(8) v 28(4) ms; low, 12(6) v 17(3) ms; high, 6(2) v 8(2) ms; p < 0.05 for all comparisons). CONCLUSIONS–These findings suggest that there is abnormal autonomic influence on the heart in patients without coronary artery disease at risk of sudden cardiac death. Hourly analysis of heart rate variability throughout the 24 hour period may provide additional information important in the identification of high risk patients.